Overconfidence and Initial Public Offering (IPO) decisions: a behavioural corporate finance survey among polish managers - Rzeszutek, Marcin; Szyszka, Adam (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2020)
Objective. The aim of this study was to examine whether corporate managers, i.e. chief executive officers (CEOs) and the chief financial officers (CFOs) of the companies listed on the Main Market of the Warsaw Stock Exchange (WSE) are susceptible to overconfidence bias and whether their overconfidence is related to their managerial practices in the process of going public (Initial Public Offering, IPO). Methods. A survey methodology was employed to identify the existence of overcon-fidence bias and to investigate the IPO managerial practices among the study participants. Fully completed surveys were obtained from 163 corporate managers. Results. The Polish corporate managers displayed overconfidence bias and also revealed several irrational managerial practices connected with IPO decisions. Importantly, the authors observed the connection between managerial overconfidence and some elements of the IPO practices among the study participants. Conclusions. It appears that even well-educated corporate managers with a high level of expertise who represent publicly listed companies, are susceptible to overconfidence bias. This may be related to their irrational managerial practices in the area of IPO decisions. Further research on behavioural corporate finance is needed to better understand the psychological obstacles that face managers in their everyday decisions regarding a company’s value creation
Argumenta Oeconomica, 2020, Nr 1 (44), s. 227-255